The Psychometric Aspects of Adolescents\' Attitude Scale toward Addiction - Hassan Rafiei; Ali Reza Jazayeri; Mohammad Ali Nazari; Leila Soleimani-Nia (University of Social Welfare and Rehabilitation Sciences, 2007)
Objective: Attitude modification is a known way in substance abuse prevention. in order to assessment of adolescents, attitude toward addiction, addict and drugs, and evaluation of their changes caused by preventive interventions , a scale was designed and its psychometric characteristics were evaluated. Materials & Methods: This study performed as an analytical design into two stages: items supplementation and experimental performance. Eighty students (aged 11-16 years old) were studied. They were classified into criterion (38 students) and control (36 students) group on the basis of their or not usage of drugs.  Results: Comparison of two groups (criterion and control) who answered the scale indicated that 52 items had good validity. After evaluation of inter consistency of the scale, 43 items were remained which differentiated adolescent with positive or negative attitude toward addiction, in cut off point 95. At this point sensitivity and specificity were 93.1 and 96.3, respectively. Conclusion: In this study the scale of adolescent attitude toward addiction was designed with results indicating that scale has a good psychometrics characteristic in Iranian adolescent population.